Chop and tumble nucleotomy – A technique for safe nuclear emulsification in posterior polar cataract - Jeewan S Titiyal; Manpreet Kaur; Sridevi Nair (Indian Journal of Ophthalmology, 2023)
A modified phaco chop technique for nuclear emulsification in posterior polar cataracts with nuclear sclerosis that avoids hydrodissection or nuclear rotation has been described. After performing a vertical chop maneuver to divide the nucleus, two pie-shaped nuclear fragments are removed from either side of the initial chop. The remaining nuclear fragments are then sequentially tumbled toward the center using the second instrument and emulsified while maintaining an intact epinuclear shell, which safeguards the fragile posterior capsule. The technique was successfully performed in 62 eyes of 54 patients with posterior polar cataract and grade II–IV nuclear sclerosis. The Chop and Tumble nucleotomy is a safe and effective technique for phacoemulsification in posterior polar cataracts with nuclear sclerosis, where hydrodissection and nuclear rotation are typically avoided.